Advancing cloud security: Unveiling the protective potential of homomorphic secret sharing in secure cloud computing - Sijjad Ali; Shuaib Ahmed Wadho; Aun Yichiet; Ming Lee Gan; Chen Kang Lee (Egyptian Informatics Journal)
Cloud computing security and data protection are becoming increasingly critical as its use increases. The research we present demonstrates how undercover sharing techniques and homomorphic encryption can be combined to protect private information in cloud computing scenarios. We create a reliable, private, and confidential computation platform by utilizing this dual approach. Our strategy involves protecting data while dividing it among multiple servers. By using this distribution, the system is less likely to suffer from single points of failure and has a higher security level. To ensure information privacy and security, data encryption restricts access to authorized individuals only. As an additional feature, we employ homomorphic encryption to enable operations on encrypted data without direct access to the originals. By using this feature, sensitive data is protected from disclosure or misuse while being processed. Therefore, original data confidentiality can be preserved when computing on encrypted shares. Several performance tests were conducted to prove our strategy’s practicality and effectiveness. Our considerations extended beyond encryption and decryption time and processing overhead. In our research, we demonstrate that our method strikes the right balance between security and computational efficiency.